FRI-4 carbapenemase-producing Enterobacter cloacae complex isolated in Tokyo, Japan. (30th July 2018) - Kubota, Hiroaki; Uwamino, Yoshifumi; Matsui, Mari; Sekizuka, Tsuyoshi; Suzuki, Yasunori; Okuno, Rumi; Uchitani, Yumi; Ariyoshi, Tsukasa; Aoki, Wataru; Suzuki, Satowa; Kuroda, Makoto; Shinkai, Takayuki; et al.
Abstract: Objectives: A carbapenem-resistant Enterobacter cloacae complex isolated in Tokyo, Japan, produced a carbapenemase that was detected by a Carba NP test and a modified carbapenem inactivation method, but none of the 'Big Five' carbapenemase genes was detected by PCR. This study aimed to identify the carbapenemase. Methods: Carbapenemase genes were screened by WGS. Next, we generated a recombinant plasmid in which the carbapenemase gene was inserted. We also extracted the carbapenemase gene-carrying plasmid from the E. cloacae complex. The effects of both plasmids on the antibiotic susceptibility of Escherichia coli were then tested. The carbapenemase gene-carrying plasmid in the E. cloacae complex was completely sequenced. Results: A novel carbapenemase gene, bla FRI-4, encoded an amino acid sequence that was 93.2% identical to French imipenemase (FRI-1). E. coli transformed with bla FRI-4 showed reduced carbapenem susceptibility. A complete sequence of the bla FRI-4 -carrying 98 508 bp IncFII/IncR plasmid (pTMTA61661) showed that bla FRI-4 and the surrounding region (18.7 kb) were duplicated. Conclusions: The FRI-4-producing E. cloacae complex was isolated in Japan, whereas all other FRI variants have been found in Europe, suggesting that the spread of FRI carbapenemases is global.